Untangling Intra-State Armed Conflict Dynamics: Typologies of Conflict in Syria’s Early Crisis (2011–2014) - Luerdi Luerdi (Indo Publishing, 2026)
Among the Arab Spring revolutions, the case of Syria could be the one that retained global attention due to its impact on regional instability and humanitarian crisis. The long-lasting conflict, originating from demand for regime change in the country, involved the armed groups and was fueled by the intervention of great powers along with other external actors since the beginning in 2011. This study aims to describe typologies of conflict, taking the Syrian conflict as a case study, focusing on the competing interactions between the armed groups and placing it as an intra-state conflict during its first four years, from 2011 to 2014. This study employed the qualitative case study approach and armed conflict typologies to address the question. The results show that Syria’s conflict was very complex, in which most of the armed groups fought against one another. While the conflict was leading to a form of war by intensity, it also represented other types of conflicts, such as civil war, state-formation or secessionist conflict, and non-state armed conflict.